Sex Sells! Could Sex Scenes in Ghanaian Video Films be used to Market Culture through Costume? - Adzovie, Daniel Edem; Jibril, Abdul Bashiru; Adzovie, Rita Holm; Aboagye, Divine Narkotey (Technium Social Sciences Journal, 2020)
Film, although one of the youngest art forms, influences societies due to its unique way of interacting with the viewer. Film directors employ different tropes in conveying messages to audiences. One of such tropes is costume. “Sex sells” is a popular expression in advertising and marketing communications. The purpose of this study is to offer a new perspective on how sex scenes in films could be used to project aspects of a country’s culture. Riding on this popular expression, we argue that sex scenes in a Ghanaian video film could be a strong fulcrum to expose aspects of the rich Ghanaian culture to the world. We submit that by paying particular attention to the mise-en-scene of costume used during sex scenes, directors could lure film lovers into appreciating the kinds of fabric as well as style used by characters in a film. Through the case study method, we reviewed literature on mise-en-scene of costume in film, and its ability to convey underlying messages to the viewer. The literature review serves as the basis of our argument, where we propose how to ride on costume in sex scenes to project and market the richness of Ghanaian culture regarding clothing/costume in sex scenes in films. In this regard, we have been able to problematize a new way of thinking about sex scenes in films, especially regarding sex scene costume as a unique selling proposition and its contribution to marketing a country’s culture to the viewing public. This study contributes to policy in the entertainment industry in terms of portrayal of sex scenes in Ghanaian video films while ensuring cultural adaptability and growth.